Enantiomeric composition of essential oils Ocimum L. components - Sachyuka T.; Kovalenko N.; Supichenko G.; Bosak V. (Техника и технология пищевых производств)
Basil Ocimum L. belongs to the perspective aromatic and essential-oil plants. Its green mass and essential oils can be successfully used in different sectors of economy including food industry. In 56 samples of basil Ocimum L. having different ecological and geographic origin the author determined the content and yield of essential oils. The study of the taken basil cultivars shows that the content of essential oils in different types of basil (sweet basil – Ocimum basilicum L., holy basil – Ocimum tenuiflorum L., camphor basil – Ocimum kilimandscharicum Willd., hoary basil – Ocimum canum Sims.) was 0.28–0.83% when its yield was 24.0–314.6 kg/ha and green mass yield during technological maturity phase (massive flowering) was 0.51–5.08 kg/m2. By means of gas liquid chromatography method the author performed compositional and anantiometric analysis of the composition of the essential oils obtained from the new basil varieties such as Ocimum L. (Magiya, Volodar, Nastena, Istochnik), bred in Belorussian State Agricultural Academy and catalogued in the National Register of Cultivars in the Republic of Belarus. As a result of the research the author determined that essential oil samples obtained from the new basil cultivars have up to 20 components. The main components are linalool, methyl chavicol, - and -pinenes, -terpineol, eugenol, geraniol, geranial, geranyl acetate, thymol, neral, carvone, carvacrol, limonene and 1.8-cineol. Enantiomers are present in essential oil components - and -pinenes, limonene and linalool.